Congenital Eccrine Angiomatous Hamartoma: A Rare Entity Revisited - Mendiratta, Vibhu (Indian Dermatol Online J, 2018)
Eccrine angiomatous hamartoma (EAH) is a rare benign malformation characterized by eccrine and vascular components. It usually presents at birth or during early infancy or childhood on lower extremities as a nodule or plaque. We report a case of asymptomatic tumoral swelling over the left leg in a 5-month-old Indian infant since birth. This was diagnosed as EAH on histopathology and confirmed on immunohistochemistry.